Shakespoke: Selves, Others, and Folk Poetry - Greenhill, Pauline (Ethnologies, 1993)
This essay introduces the six papers in this special issue by comparing the writers’ construction of analytical and rhetorical distance from their subjets — folk poetry and folk poets — in terms of concepts of self and other. It focuses upon folklorists as the (re)producers of cultural texts, not only as their disengaged audience.